Needs assessment and development of intervention to improve food safety behavior among food handlers in selected school canteens in the Klang Valley, Malaysia - Wong, Stephenie Yoke Wei (2021)
In Malaysia, the number of foodborne outbreaks in schools has increased over the years. One of the main contributing factors is the improper handling of food among food handlers. The study aimed to develop an intervention to improve two selected food safety behaviors (handwashing and preventing contamination of ready-to-eat food) among food handlers at public school canteens. An-extended Health Action Model (HAM) was used as a framework to conduct a needs assessment, using a mixed-method approach comprising of focus group, survey and direct observation. A total of seven focus group discussions with food handlers (n=64) were first carried out to identify their perceived barriers and motivation to perform handwashing and preventing food contamination, which were used as part of the instrument adaptation and validation process. This was followed by a baseline survey (n=211) on food handlers’ knowledge , belief, norm, motivation, habit, and behavioral intention according to the HAM constructs. The proposed research model extends HAM by incorporating five dimensions of beliefs (i.e., self-efficacy, perceived susceptibility, severity, barriers, and benefits) and four dimensions of motivation (law and enforcement, reward, internal motivation, and resources). Analysis using PLS-SEM (v3.0) revealed that norm and knowledge significantly influenced belief, ultimately affecting food handlers’ intention